Сучасна політика України у сфері виконання покарань у контексті застосування до засуджених, позбавлених волі, заходів фізичного впливу, спеціальних засобів і зброї - Охман, О.; Ohman, O. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
В статті здійснений аналіз правових засад та практики реалізації у кримінально-виконавчій діяльності України заходів безпеки (фізичної сили, спеціальних засобів та зброї) до осіб, які тримаються у слідчих ізоляторах та кримінально-виконавчих установах закритого типу, а також запропоновані науково обґрунтовані заходи щодо вирішення існуючих у цій сфері проблем. In the article author analyzed the legal grounds and practice of security measure’s using in the penal activities of Ukraine (physical force, special means and weapons) to persons, who are held in detention centers and penal institutions of the closed type, and proposed scientifically justified measures, directed at solving the existing problems in this area. Penal policy is realized on the basis of the norms of law branches, each of which has its own specifics and a certain effect on the forms and methods of its implementation. In particular, in the theoretical aspect, this gives grounds for separation in politics of fighting against crime, as an integrated social regulatory system, its individual subsystems of criminal law, criminal procedure, criminal-executive and criminological policy. Solution of problems of public policies to combat crime, especially in the application of criminal law is not limited to issues of quality and efficiency of the latter. To achieve the necessary security for the state of society from criminal encroachments is possible only through a broad and complex range of measures fighting against crime: organizational, legal and administrative (as a manifestation of political will); socio-economic, cultural and naturally-humanic; specifically, legislative, methodological, legal and criminological. Organizational, legal and administrative and management measures by which the State focuses on the fighting against crime are of great importance. Law-enforcement activity may significantly affect the performance’s indicators of fighting against crime.
The Current Policy of Ukraine in the Sphere of Punishment’s Execution in Context of Applying to Convicted, Deprived of Their Liberty, the Measures of Physical Influence, Special Facilities and Weapons.
Keywords: безпека; фізична сила; спеціальні засоби; зброя; правові підстави; ув’язнений під варту; засуджений до позбавлення волі; виправна колонія; Державна кримінально-виконавча служба України; security; physical strength; special tools; weapons; legal basis; taken into custody; sentenced to imprisonment; penal colony; Penal Service of Ukraine